The Developmental Tendency in Educational Research - Montvilaitė, Sigita (Acta Paedagogica Vilnensia, 2005)
Determining the present status and perspective of science it is important to take into consideration its evolution. The article reveals the developmental tendencies of educational science and the problem is highlighted within the frame of origin, formation and history development of scientific research paradigms. The attention is paid to the present general policy of science, which is directly connected with development possibilities of science of education in Lithuania. In order to show the roots of this problem, this article maintains the influence of a classical paradigm of research. In order to deny the forced incriminations to the science of education, the general criteria of scientific character are presented in this present article. The following truth is justified that the science of education, having its independent subject of investigation, its own object and particular scientific method functions in its full capacity and executes all functions meeting the science.